Peningkatan Hasil Belajar Siswa Kelas IX-A Pada Pelajaran Bahasa Indonesia Materi Melaporkan Peristiwa Dengan Menggunakan Metode Think Pair Share - Kartini, Kartini (Efektor, 2019)
Indonesian Language learning in SMP Negeri 3 Kediri, especially in class IX-A SMP Negeri 3 Kediri in the academic year 2016/2017 has several obstacles in the learning process. In the first semester, the results of student learning were still low so that they did not reach the value of the KKM Indonesian language lesson which was 78. One way that can be done by the teacher is to use a new learning method. The learning method is Think Pair Share. Think Pair Share is a method that emphasizes students to discuss with pairs (pairs) to solve the problems given by the teacher, students share (share) with their classmates by presenting their opinions with their partners. The application of this method starts with the teacher giving the task to the students to prepare a report of events, then students in small groups of 2 students. Students compile reports of events and then read them in front of the class. This method can train student cooperation because students share with their friends in compiling reports and also practice courage, especially in reading reports of events in front of their friends. This classroom action research aims to improve student learning outcomes. The indicator of the success of this study is that 75% of students pass KKM. Based on research data, it can be seen that there are 45% (15) students completing KKM. Then, in the first cycle, there are 70% (23) students complete KKM. Then, in the second cycle, there were 79% (26) students completed KKM. The data showed an increase from pre-cycle to cycle II. And the success of the study is in accordance with the indicators of success obtained during cycle II, which is 79% of students complete KKM or more than 75% of students complete KKM